THE EFFECTS OF PACK CARBURIZING USING CHARCOAL ON PROPERTIES OF MILD STEEL - Supriyono, Supriyono (Universitas Muhammadiyah Surakarta, 2018)
The aim of this research is to study the effects of pack carburizing using charcoal on properties of mild steel. The properties are represented by the results of microstructure, hardness test and tensile test. Â The carburizing process was conducted in the temperature of 930oC which is the austenite temperature of the mild steel. The source of carbon was charcoal. The specimens were held for 2, 3 and 4 hours at the carburizing temperature. The carbon content of the raw amterial was 0.17%. The raw material was hypoeutectoid steel with ferrite and pearlite phases in its microstructure.Â After the carburizing process, the microstructure can be divided into two zones e.i. case zone and core zone. The case zone consists of hypereutectoid, eutectoid, and hypoeutectoid sub-zone. The core zone is the same as raw material. The longer the holding time will result in the deeper the case zone and the stronger the material.